2022
DOI: 10.5430/wjel.v12n2p382
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Collocation in Creative Writing among Pakistani Learners at Secondary Level: A Corpus-based Study

Abstract: Research works on the usage of lexical collocations for enhancing the creative writing of foreign language learners is considerably lacking. To examine the impact of collocation on reading, speaking and writing skills have been the focus of the researchers. It was observed that the writing skill of EFL learners was weak and they faced difficulties in English writing. Pakistani EFL learners are facing problems while writing English creatively especially at secondary level. Their writing is weak due to lack of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This application of language helps reinforce vocabulary, grammar, and sentence structure, leading to improved language proficiency. Additionally, creative writing assignments require students to communicate authentically, often in contexts that mirror real-life situations (Akhter & Nordin, 2022). This type of practice helps bridge the gap between classroom learning and real-world language use.…”
Section: Evidence On the Use Of Creative Writing Assignments In A Sec...mentioning
confidence: 99%
See 1 more Smart Citation
“…This application of language helps reinforce vocabulary, grammar, and sentence structure, leading to improved language proficiency. Additionally, creative writing assignments require students to communicate authentically, often in contexts that mirror real-life situations (Akhter & Nordin, 2022). This type of practice helps bridge the gap between classroom learning and real-world language use.…”
Section: Evidence On the Use Of Creative Writing Assignments In A Sec...mentioning
confidence: 99%
“…It offers a unique and effective approach to language learning by combining linguistic skill development with creative expression (Tu, 2021). Specifically, creative writing contributes to the development of language skills in multilingual students by enhancing their vocabulary, improving grammar and syntax, boosting cultural exploration, critical thinking, problem-solving, creativity and imagination (O'G'Li, 2021;Akhter & Nordin, 2022). Incorporating creative writing into language instruction for multilingual students can be a powerful tool for language acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate learners, on the other hand, showed a tendency towards inferencing and contextual guessing, suggesting a developing ability to grasp overall meaning from context. Advanced learners predominantly utilized global strategies like skimming for gist and critical evaluation, indicative of a higher-level comprehension and engagement with the text [8][9][10]. Intriguingly, the study revealed that certain strategies, like scanning for specific information, were consistently used across all levels, underscoring their fundamental role in reading comprehension.…”
Section: Analysis Of Reading Strategiesmentioning
confidence: 99%
“…Since that time, countless deviations have arisen; movements in English and thought have emerged in various nations. In spite of all these changes, the process of communication not stopped (Akhter & Nordin, 2022). Social media gives opportunity to its followers allows users to share their views with others in a simple and organised manner using a diversity of electrical and rechargeable diplomacies, such as tablets, smartphones, and computers.…”
Section: Introductionmentioning
confidence: 99%